Solo Kid's Space Sebagai Fasilitas Ruang Bermain Dan Belajar Anak Di Surakarta - Fathana Kunti, Astrid, Rini Hidayati, ST, MT (2016)
Abstracts Children aged 1-12 years need a trigger creativity and knowledge. Triggers can children's creativity through playing. As for enhancing children's knowledge of reading books. Unfortunately, the children's interest in Indonesia is very low. Toys educative impact both for children as it can be to keep emotions, understand instructions and receive knowledge. Solo city itself has not had a special container children to explore imagination and creativity. For this reason came the idea to create a place for children who can accommodate all activities of reading, listening, distribution of talent, socializing and creativity of children through toys that Solo Kid's Space. Solo Kid's Space is playing and educational facility for children that combines the commercial and public facilities. Its main activity is the sale of toys and children's books, education by reading books or listening to fairy tales, recreation with play, get to know new things or talents, and socializing. The main activity is focused on children ages 1-12 years. Keywords: playing facilities, learning and child